An assessment of pharmacy practice in Libya measured against international standards - Ali, Mohammed; Benkorah, Amal (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Introduction: Practicing pharmacy in Libya is still limited to the dispensing roles. However, pharmacists have started to work proactively to advance modern practices by expanding their roles in different practice settings. Objective: This study aims to evaluate the status of pharmacy practice in Libya through self-assessing competencies of hospital and community pharmacists. Materials and Methods: This is a cross-sectional online survey study of community and hospital pharmacists. The survey questionnaire was based upon the “Global Competency Framework for Pharmacists̶ and the Joint FIP/WHO guidelines on good pharmacy practice. Results: A total of 199 responses were received with 93% response rate. 47.0% were community pharmacists, 39.4% worked both in hospital and community, and 13.6% practiced exclusively in hospitals. 10% of respondents graduated in 1980–1989; 15% graduated in 1990–1999. 30% graduated in 2000–2009, and 45% graduated in the past 8 years before the study (2010–2017). The overall pharmacy competency indicators were reportedly met consistently by 45.3% of respondents, usually by 25% of responders and only sometimes or rarely by 15.9% or 13.8% of respondents, respectively. Conclusions: Pharmacy practice in Libya is more population and system-focused than being professional and patient-focused. Significant amendments in pharmacy education curricula are required to include modern teaching methods, knowledge, skills, and competencies. Continuous professional development programs are also needed for established pharmacists to modernize pharmacy practice in the country.
Keywords: Competency; framework; Libya; pharmacists; pharmacy practice